Internal flesh browning of ‘Cripps’ Pink’ apple (Malus domestica Borkh.) as influenced by pre-harvest factors and the evaluation of near infrared reflectance spectroscopy as a non-destructive method for detecting browning - Butler, Leana (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.